2017
DOI: 10.1016/j.metabol.2017.01.030
|View full text |Cite
|
Sign up to set email alerts
|

The short-term and long-term effects of bariatric/metabolic surgery on subcutaneous adipose tissue inflammation in humans

Abstract: Context The mechanisms mediating the short- and long-term improvements in glucose homeostasis following bariatric/metabolic surgery remain incompletely understood. Objective To investigate whether a reduction in adipose tissue inflammation plays a role in the metabolic improvements seen after bariatric/metabolic surgery, both in the short-term and longer-term. Design Fasting blood and subcutaneous abdominal adipose tissue were obtained before (n=14), at one month (n=9), and 6–12 months (n=14) after bariatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 64 publications
(46 citation statements)
references
References 68 publications
(87 reference statements)
1
36
1
2
Order By: Relevance
“…There may also be changes in serum levels of the insulin sensitizing hormone adiponectin following bariatric surgery. While Sams et al (407) observed significant increases in circulating adiponectin two weeks following surgery, our studies revealed no improvement one to 12 months post-surgery (162, 254). …”
Section: Adipose Tissue Inflammation and Insulin Resistancecontrasting
confidence: 85%
See 4 more Smart Citations
“…There may also be changes in serum levels of the insulin sensitizing hormone adiponectin following bariatric surgery. While Sams et al (407) observed significant increases in circulating adiponectin two weeks following surgery, our studies revealed no improvement one to 12 months post-surgery (162, 254). …”
Section: Adipose Tissue Inflammation and Insulin Resistancecontrasting
confidence: 85%
“…Clear reductions in CRP are more apparent three to four months post-operatively, when presumably surgery-related inflammation has subsided (52, 202, 488), even though this is not seen in all studies (310, 483). Six to 12 months post-surgery, CRP, IL-6, PAI-1, and MCP-1 consistently are reduced relative to pre-surgery levels (6, 28, 108, 157, 162, 181, 199202, 254, 310, 323, 327, 368, 468, 483, 489). There may also be changes in serum levels of the insulin sensitizing hormone adiponectin following bariatric surgery.…”
Section: Adipose Tissue Inflammation and Insulin Resistancementioning
confidence: 88%
See 3 more Smart Citations